(untitled) (Al-Academy, 2025)
The current research (cultural awareness in contemporary painting and its manifestations in the products of art education students) dealt with investigating post-modern art trends, which witnessed transformations in artistic achievements after 1940, that is, after World War II, and the emergence of artistic trends that are commensurate with scientific and technological progress and openness of awareness. Cultural influence on the various techniques that the West witnessed in the second half of the twentieth century, especially in the field of arts through visual experiments (drawing). The first chapter included the methodological framework for the research, while the second chapter contained two sections: The first section included: the concept of cultural awareness, and the second section included cultural awareness in post-modern trends represented by (abstract expressionism, popular art, and graffiti art). The third chapter contained research procedures including (research population, research samples, research methodology, sample analysis), where the research sample of (3) samples of master’s students in the Department of Art Education was analyzed. The fourth chapter contained (research results, conclusions, recommendations, and proposals). key words . Cultural awareness, post-modern trends, representations